Coparenting Alleviated the Effect of Psychological Distress on Parental Psychological Flexibility - Yu, Yongju; Xiao, Yan (Frontiers in Psychology, 2021)
Parenting is full of challenges and responsibilities. It is particularly important for parents to be open to parental difficult experiences and adopt behaviors consistent with self-chosen values, which termed as parental psychological flexibility (PPF). However, few studies have focused on the effect of psychological distress (anxiety and depression) on different components of PPF. This study examined the effect of psychological distress on the three components of PPF (cognitive defusion, committed action, and acceptance) as well as the role of coparenting quality in Chinese parents. A total of 462 parents of children aged 1-18 years completed self-report measures of anxiety, depression, coparenting, and PPF. Our results revealed that higher level of PPF went along with less anxiety and depression, while it was also associated with better coparenting quality. Coparenting partially mediated the effect of anxiety on cognitive defusion and acceptance and fully mediated the effect of depression on cognitive defusion and acceptance. Moderation analyses showed that the link between anxiety and cognitive defusion, as well as the link between anxiety and acceptance were moderated by coparenting. We discussed the implications of coparenting as a protective factor in alleviating the negative effect of psychological distress on PPF.